Maximizing Success With Rapid Sequence Intubations. (July 2018) - Smith, Tony L.; Van Meter, Jessica
Abstract : Within emergency care settings, rapid sequence intubation (RSI) is frequently used to secure a definitive airway (i.e., endotracheal tube) to provide optimal oxygenation and ventilation in critically ill patients of all ages. For providers in these settings, a deeper understanding of the indications, associated medications, and adjunctive techniques may maximize success with this common procedure. Identification of difficult airways, using mnemonics and standardized criteria prior to the procedure allows, the clinician additional time for assimilation of additional resources and tools to increase the likelihood of first-pass success with intubation. This article describes tools for the procedure of RSI, including the "7 Ps" checklist of intubation.